Difficult Texts: Romans 9.13: 'Jacob I loved, and Esau I hated'. Issue 1 (January 2018) - Phillips, Anthony
Neither Paul nor Malachi, whom he quotes, appears concerned that God should choose a trickster over his elder brother. But for the Hebrews, deception could be regarded as an act of wisdom which the parable of the unjust steward appears to confirm.